Mitigation of The Risk of Failed Harvest Pond Farming Fisheries Using The Calculating of The Premium Through The Approach to The Principle of Expectation Value - Fadia Irsya Septiana; Dwi Susanti; Sukono Sukono (Research Collaboration Community (RCC), 2023)
Pond cultivation is a promising business to be engaged in at this time, the demand for fish in the market is high, it opens opportunities for entrepreneurship in the field of fish cultivation. It is undeniable that several factors will cause crop failure in fish farming, both from weather factors and in the livestock process. If such an unexpected thing happened, the cultivators would be slightly affected. Therefore, there is a need for special insurance to protect farmers from financial losses due to possible risks, namely Fishery Microinsurance. This study aims to determine a reasonable amount of insurance premiums for small-scale shrimp pond aquaculture cultivators using the expectancy value principle calculation method. The data on the number of events uses the Poisson distribution, while the loss data uses the Exponential distribution in Pandeglang Regency. Next use the Maximum Likelihood Estimation method to calculate the parameter estimate. After that, the results of the parameter estimation are used to search for a collective risk model. Thus, the result of the premium calculation in this study was Rp 25.893.046